2019
DOI: 10.1002/eji.201848000
|View full text |Cite
|
Sign up to set email alerts
|

The role of Eomes in human CD4 T cell differentiation: A question of context

Abstract: Eomesodermin (Eomes) is a transcription factor (TF) of the T-box family closely related to T-bet known for its role in CD8 T cell and natural killer cell differentiation. However, the role of Eomes in CD4 T-cell differentiation is less well appreciated. In this issue of the European Journal of Immunology[Eur. J. Immunol. 2019. 49: 79-95] Mazzoni et al. and [Eur. J. Immunol. 2019. 49: 96-111] Gruarin et al. studied the role of Eomes in human CD4 T-cell differentiation. Mazzoni et al. showed that Eomes plays a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 15 publications
3
33
0
Order By: Relevance
“…Previous studies have suggested that EOMES and RUNX3 contribute to the development and homeostasis of effector and memory T cells as well as NK cell differentiation. [40][41][42] Nevertheless, the role of XBP1 in regulating cytotoxic lymphocytes is less well understood, [43][44][45] and the effects of these regulators in immune responses have not been addressed in NPC. To validate the SCENIC results, we isolated CD8 + T cells and NK cells from the NPC tissue samples by flow cytometry (FACS), and identified a significantly higher percentage of cytotoxic GZMB + or perforin + phenotypes in the EOMES + , RUNX3 + , and XBP1 + CD8 + T cells and NK cells (Supplementary information, Fig.…”
Section: Correlations Of Malignant Signatures With Tumor Characteristmentioning
confidence: 99%
“…Previous studies have suggested that EOMES and RUNX3 contribute to the development and homeostasis of effector and memory T cells as well as NK cell differentiation. [40][41][42] Nevertheless, the role of XBP1 in regulating cytotoxic lymphocytes is less well understood, [43][44][45] and the effects of these regulators in immune responses have not been addressed in NPC. To validate the SCENIC results, we isolated CD8 + T cells and NK cells from the NPC tissue samples by flow cytometry (FACS), and identified a significantly higher percentage of cytotoxic GZMB + or perforin + phenotypes in the EOMES + , RUNX3 + , and XBP1 + CD8 + T cells and NK cells (Supplementary information, Fig.…”
Section: Correlations Of Malignant Signatures With Tumor Characteristmentioning
confidence: 99%
“…To better understand the specific phenotypic attributes of polyfunctional Mtb300-specific CD4 T cells expressing CD153, we compared the expression of CD27 (memory marker), HLA-DR (activation marker), KLRG1 (coinhibitory molecule), 14 and Eomes (Transcription factor) 15 in CD153+ IFNγ+ TNFα+ IL-2+ and CD153− IFNγ+ TNFα+ IL-2+ Mtb300-specific CD4 T cells in our four study groups (Fig. 5a).…”
Section: Phenotypic Characteristics Of Polyfunctional Mtb300-specificmentioning
confidence: 99%
“…In cooperation with other factors like PR domain zinc finger protein 1 (BLIMP1), EOMES is a driver of IL-10 production in T R 1 T-cells in mice (7) as well as humans (8). Whether EOMES only promotes Il10 expression by T R 1 cells or is a lineage-defining transcription factor is still unclear (35).…”
Section: Introductionmentioning
confidence: 99%